Patient brokering in for-profit substance use disorder treatment: a qualitative study with people with opioid use disorder and professionals in the field - Sarah E. Clingan; Brittany M. D’Ambrosio; Peter J. Davidson (BMC Health Services Research, 2023)
Abstract Background Opioid use and opioid overdose deaths are at an all-time high and evidence-based treatments for people with opioid use disorder (OUD) are underutilized. Therefore, we sought to understand experiences and perceptions of abuses in the for-profit substance use disorder treatment industry that could potentially put people with OUD at an increased risk for an overdose. Methods One-on-one semi-structured interviews were conducted from November 2018 to May 2019 in Southern California with 20 people with OUD and 20 professionals who work in the substance use disorder (SUD) treatment field. A grounded theory approach was conducted to discover emerging patterns from the data. Results Three major themes emerged:1) financial and material enticements, 2) encouraging substance use in the for-profit treatment sector, and 3) contributors to overdose risk. Participants reported that patient brokers would pay for plane tickets and offer financial incentives (e.g., money) to attract individuals to SUD treatment, capitalizing on insurance profits despite initial expenses. Participants reported being encouraged to use drugs before treatment to meet insurance conditions, thus jeopardizing genuine recovery efforts and adding to the temptation of drug use. Many participants linked patient brokering to increased overdose deaths, emphasizing the dangerous practices of brokers providing drugs, promoting relapse, and creating a revolving door of treatment, which compounds the overdose risk after periods of abstinence. Conclusions Patient brokering and unethical abuses in the for-profit treatment industry have caused some people with OUD to seek treatment for money and housing instead of seeking treatment to stop opioid use. The harmful treatment environment was seen as a barrier to care and an unwanted obstacle to overcome on the path to recovery.